Melanoma vaccines - Mackiewicz, Andrzej; J. Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2003)
Malignant melanoma is an immunogenic tumor, and its spontaneous remissions are associated with activation of the immune system. Discovery of this fact induced a rapid progress in the field of immunology of this cancer and in the development of novel strategies of immunotherapy. Characterization of immune mechanisms responsible for recognition and rejection of cancer cells paved the way for construction of melanoma vaccines. Up to now, the efficacy of different types of melanoma vaccines (antigenic, cellular, DNA, GMTV, DC) has been analyzed in numerous clinical trials. However, results of these trials are still unsatisfactory. As yet there is no phase III clinical trials that demonstrated a statistically significant difference between vaccine and control groups in term of overall – (OS) and disease free survival (DFS). Signs of immune system activation that has been observed in patients receiving melanoma vaccines did not correlate with clinical outcomes. In a clinical trial carried out in our department since 1995 we have been evaluating the efficacy of GMTV modified with a gene complex encoding IL-6 and sIL-6R. In the phase II trial the 60% response rate was achieved (CR – 15%, PR – 15%, SD – 25%). The DFS of patients immunized after surgical removal of metastases has been extended from 7 to 24 months. The OS cannot has not been determined yet, since the majority of patients is still alive (observation time ~4 years). In January 2004 we will begin recruitment of patients for the phase III clinical trial (randomized, double-blind, placebo controlled study). The study will be carried out in main polish oncology centers.